The nexus of E-government and increased productivity relative to income level comparison - Faid, Gul; Tariq, Majeed Muhammad; Ishtiaq, Ahmad; Zeynvand, Vahid Lorestani; Meyer, Daniel Francois; Máté, Domicián (Business, Management and Economics Engineering, 2020)
Purpose – this study aims to determine the influence of E-government on productivity in the case of different countries comparing by income level. Research methodology – static (fixed and random) and dynamic (GMM) panel regression. Findings – a disaggregated analysis reveals that middle-income countries are driving global productivity growth by implementing ICTs infrastructure in the public sector. Research limitations – this study focuses on severe developed and developing economies, whereas each country may not benefit from E-government implementation as gains might be offset with the enormous costs of implementation. Practical implications – the government may rely more on online services in the provision of its responsibilities because it enhances the efficiency of public sectors. Originality/Value – the study is a novel measure of E-government that covers additional multiple dimensions.